Robust Stability of Switched Delay Systems with Average Dwell Time under Asynchronous Switching - Jun Cheng; Hong Zhu; Shouming Zhong; Yuping Zhang (Journal of Applied Mathematics)
The problem of robust stability of switched delay systems with average dwell time under asynchronous switching is investigated. By taking advantage of the average dwell-time method and an integral inequality, two sufficient conditions are developed to guarantee the global exponential stability of the considered switched system. Finally, a numerical example is provided to demonstrate the effectiveness and feasibility of the proposed techniques.